왕겨에서 Tricin과 Tricin 4"-O-(threo-β-guaiacylglyceryl) Ether(TTGE) 추출 조건의 최적화 - 윤나라(Nara Yoon); 이상훈(Sang Hoon Lee); 장귀영(Gwi Yeong Jang); 이윤정(Yoon Jeong Lee); Li Meishan; 김민영(Min Young Kim); 이준수(Junsoo Lee); 정헌상(Heon Sang Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
This study was conducted to evaluate the effects of extraction conditions on tricin and tricin 4'-O-(threo-${β}$-guaiacylglyceryl) ether (TTGE) extracted from rice hull (Oryza sativa L.). Extraction conditions were an ethanol concentration of extraction solvent of 50~90%, extraction time of 0.5~48 h, and ultrasonic-assisted and agitated extraction as extraction methods. The total tricin and TTGE contents of rice hull were $82.20μg/g$ and $53.12μg/g$, respectively. Recovery of tricin and TTGE increased to 76.11% and 71.42% with increasing ethanol concentration until 70% and then decreased above 80%, respectively. In ultrasonic-assisted extraction, highest recovery of tricin was 83.30% after 2 h of extraction and TTGE was 71.80% after 1 h of extraction. In agitated extraction, highest recovery of tricin was 92.34% after 48 h and TTGE was 76.89% after 24 h of extraction. Therefore, optimum extraction conditions for tricin and TTGE of rice hull were 70% ethanol concentration and ultrasonic-assisted extraction for 1 h. 본 연구에서는 왕겨 중의 tricin과 TTGE의 함량을 확인하고, 추출용매의 에탄올 농도(50, 60, 70, 80 및 90%), 추출방법(교반 및 초음파 추출) 및 추출시간(0.5~48시간)이 tricin과 TTGE의 추출에 미치는 영향을 살펴보았다. 왕겨의 tricin과 TTGE의 함량은 각각 $82.20μg/g$ 및 $53.12μg/g$이었다. Tricin 및 TTGE의 최적 추출용매의 에탄올 농도 50, 60, 70, 80 및 90%에 따라 tricin은 각각 66.03, 70.70, 76.11, 66.16 및 23.99%를, TTGE는 각각 64.56, 68.14, 71.42, 60.29 및 16.84%의 회수율을 보여 70% 농도가 가장 높았다. 초음파 추출 시 tricin 회수율은 2시간 처리에서 83.30% 그리고 TTGE는 1시간 처리 시 71.80%로 높았다. 교반 추출 시 추출시간의 증가에 따라 회수율은 증가하였으며, tricin은 48시간 추출 시 92.34% 그리고 TTGE는 24시간 추출 시 76.89%로 높았다. 이상의 결과로부터 tricin과 TTGE를 가장 효율적으로 추출할 수 있는 조건은 추출용매의 에탄올 농도 70%로 1시간 초음파 추출이라 판단된다.